Study on water quality effect due to erosion and sedimentation process around Tasik Chini - C. Yahya, Che Hafiz; Nadiatul Adilah, Ahmad Abdul Ghani; Ibrahim, Saerahahy L.; Saadon, Azlinda; Tholibon, Duratul Ain; Zamri, Zamsalwani; Ariffin, Junaidah (2018)
The purpose of this study is to analyze water quality of Tasik Chini in 2017. A total of fourteen water quality parameters and twelve heavy metals were measured based on Malaysian Department of Environment Water Quality Index (DOE-WQI) and also classified according to the Interim National Water Quality Standard, Malaysia (INWQS). The physical and chemical variables such as pH, Electrical Conductivity (EC), Turbidity, Temperature, Dissolved Oxygen (DO), Total Suspended Solid (TSS), Suspended Solid (SS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammoniacal Nitrogen (NH3-N), Hardness, Nitrate (NO3-) Potassium (K), and Phosphorus (P) were analysed in-situ and using laboratory experiments. Twelve parameters of heavy metals concentration identified a Iron (III) Oxide (Fe2O3), Silicon Dioxide (SiO2), Aluminium Oxide (Al2O3, Manganese Oxide (MnO), Potassium Oxide (K2O), Titanium Dioxide (TiO2), Phosphorus pentoxide (P2O5), Barium Oxide (BaO), Lead Oxide (PbO), Calcium Oxide (CaO), Sulphur Trioxide (SO3), and Zinc Oxide (ZnO) were also tested. Results based on Malaysian WQI have shown that the water in Tasik Chini is classified as Class III, which can be used for recreational activities.Based on the land use observations done during site visits and yearly assessment using Google Earth application, the illegal logging, iron mining, industrial and agriculture activities in the surrounding area of the lake significantly affected the water quality of Tasik Chini.